(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, military intelligence was created by Soviet Russia in 1918 under the leadership of Ryuganov, the head of the intelligence department of the Turkestan Front headquarters, the department made an in-depth study of the political and military situation of the Bukhara Emirate, and this intelligence information was sent to the organizers of the "Bukhara operation" in May 1920, in the form of a secret document.